2018
DOI: 10.1371/journal.pone.0191772
|View full text |Cite
|
Sign up to set email alerts
|

The high prevalence of playing-related musculoskeletal disorders (PRMDs) and its associated factors in amateur musicians playing in student orchestras: A cross-sectional study

Abstract: ObjectiveDespite the high number of amateur musicians in the general population, little is known about the musculoskeletal health of amateur musicians. Playing a musical instrument is supposed to be a risk factor for the development of musculoskeletal complaints. This study aimed to evaluate playing-related musculoskeletal disorders (PRMDs) among amateur musicians playing in student orchestras.DesignA cross-sectional study.Participants357 members of eleven Dutch student orchestras across the Netherlands were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
3
30
0
2
Order By: Relevance
“…Indeed, PAS-QuickDASH scores of 37.5 recorded for both WP and WSP clusters, and 25.0 for both LSP and NBP clusters (Table 6) showed a wide range of scores compared to the median of the total sample (31.3). Overall, reported disability levels were high in comparison to other studies using this outcome measure among music students [40][41][42], professional orchestra musicians [6,43] or among other populations [44]. Even though this difference could be attributed to the fact that participants included in our sample were all music students with current MSK pain, the mechanisms regarding the impact of MSK pain on their functional and the relevant implications on their playing ability deserve further exploration.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, PAS-QuickDASH scores of 37.5 recorded for both WP and WSP clusters, and 25.0 for both LSP and NBP clusters (Table 6) showed a wide range of scores compared to the median of the total sample (31.3). Overall, reported disability levels were high in comparison to other studies using this outcome measure among music students [40][41][42], professional orchestra musicians [6,43] or among other populations [44]. Even though this difference could be attributed to the fact that participants included in our sample were all music students with current MSK pain, the mechanisms regarding the impact of MSK pain on their functional and the relevant implications on their playing ability deserve further exploration.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, PAS-DASH scores of 37.5 recorded for both WP and WSP clusters, and 25.0 for both LSP and NBP clusters (Table 6) showed a wide range of scores compared to the median of the total sample (31.3). Overall, reported disability levels were high in comparison to other studies using this outcome measure among music students (39)(40)(41), professional orchestra musicians (6,42) or among other populations (43). Even though this difference could be attributed to the fact that participants included in our sample were all music students with current MSK pain, the mechanisms regarding the impact of MSK pain on their functional and the relevant implications on their playing ability deserve to be explored further.…”
Section: Discussionmentioning
confidence: 69%
“…It has been shown that playing an instrument can lead to PRmDs (41–93% for professionals and 67.8% for amateurs) due to repetitive actions or sustained positions [ 31 ], which could lead to an increase in mechanosensitivity of several tissues. Recent studies have shown a positive association between pain and mechanosensitivity [ 12 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%